2005
DOI: 10.4049/jimmunol.175.6.3964
|View full text |Cite
|
Sign up to set email alerts
|

Th1-Like Cytokine Induction by Heat-Killed Brucella abortus Is Dependent on Triggering of TLR9

Abstract: In this report we provide evidence, for the first time, that bacterial DNA in the context of heat-killed Brucella abortus (HKBA) engages TLR9 in dendritic cells (DC), resulting in a Th1-like cytokine response. This is based on the findings that HKBA induction of IL-12p40 is: 1) abolished in DC from TLR9−/− mice; 2) blocked by suppressive oligodeoxynucleotides; 3) simulated by bacterial DNA derived from HKBA; and 4) abrogated by DNase or methylation of the DNA from HKBA. Furthermore, the effect of HKBA can be i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
2
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(84 citation statements)
references
References 69 publications
6
73
2
3
Order By: Relevance
“…The CyD-and CQ-induced inhibition of IL-12p40 was not secondary to cell death, as the viability of the untreated and CyD-or CQ-pre-treated DCs was 96.8%61.3% and 95.4%61.6% versus 93.9%62.7% and 92.8%63%, respectively. These data confirm the indispensable role of HKBA phagocytosis and digestion in IL-12p40 induction by DCs and further supports previous data 4 suggesting that IL-12p40 secretion by HKBA-stimulated DCs is important for the activation of TLR9 localization to the endosomes.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…The CyD-and CQ-induced inhibition of IL-12p40 was not secondary to cell death, as the viability of the untreated and CyD-or CQ-pre-treated DCs was 96.8%61.3% and 95.4%61.6% versus 93.9%62.7% and 92.8%63%, respectively. These data confirm the indispensable role of HKBA phagocytosis and digestion in IL-12p40 induction by DCs and further supports previous data 4 suggesting that IL-12p40 secretion by HKBA-stimulated DCs is important for the activation of TLR9 localization to the endosomes.…”
Section: Resultssupporting
confidence: 92%
“…Here, we investigated the effect on heat-killed Brucella abortus (HKBA) through the costimulation of two TLRs, particularly because it is known to activate both TLR2 and TLR9 in mouse dentritic cells (DCs). 4,5 We paid particular attention to the possibility that the cross-talk between two signal transduction pathways might require regulated integration for the effective induction of proinflammatory cytokines.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the decreased levels of both DCs may directly cause the negative regulation of IgG-secreting B cells in the post-6h group. Several reports have indicated that CQ can regulate innate immune functions in a TLR9-dependent manner (He et al 2004;Hong et al 2004;Coban et al 2005;Huang et al 2005). In addition, early studies in TLR9-deficient mice revealed that TLR9 was not only required for the production of pro-inflammatory cytokines, but also for the induction of Th1-based immune responses and the proliferation of B cells (Liu et al 2003;He et al 2004;Iwasaki and Medzhitov 2004).…”
Section: Discussionmentioning
confidence: 99%